EVALUASI KINERJA PRAKTIKUM TITRASI ASAM BASA DENGAN TEKNIK SELF ASSESMENT MAHASISWA FKIP UNIMAL - Hayatuz Zakiyah (UIN AR-RANIRY, 2018)
The aim of this study was to determine the ability performance of FKIP Unimal chemical education students by the using of practicum performance appraisal with self assessment techniques as well as knowing the response of students related to practical performance assessment with self assessment techniques. Self assessment is an assessment of self competence. This study was motivated by the fact that the assessment carried out in practicum activities was still centered on the lecturer and only limited to knowledge that had not been assessed by performance and did not involve students as subjects but only objects of assessment. Type of this study is descriptive qualitative. This study was conducted to describe the findings of the use of performance assessment with self assessment techniques in chemical practicum. The study was carried out at the FKIP Unimal chemical education department for students who took 23 basic chemistry labs. The result was obtained from the instrument of performance appraisal sheets and questionnaire sheets for student responses. Data analysis on the ability of practicum performance and student response of self assessment was analyzed by using percentage techniques. Based on the results of the study showed that the ability of student practicum performance by the assessment of self assessment techniques consisted of very high was about 13.04%; high was about 47.83%; and sufficient was about 39.13%. The student responses to the using of performance appraisal with self assessment techniques showed the results that most students agreed and felt happy with the self-assessment. The conclusion of this study was the students were able to assess performance with self assessment techniques and provide a positive response related to the performance assessment with self assessment techniques.